PJMHS 2021
DOI: 10.53350/pjmhs211592572
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes between Vaccinated versus Non-Vaccinated Covid-19 Patients

Abstract: Objective: To compare the outcomes in term of hospital stay and mortality between vaccinated and nonvaccinated covid-19 patients. Study Design: Prospective/Observational Place and Duration: The study was conducted at Medicine department of Fauji Foundation Hospital Rawalpindi and Pak International Medical College Hayatabad Peshawar for six months duration from December 2020 to May 2021. Methodology: One hundred ten patients of either gender with covid-19 disease were enrolled. All the patients were confirmed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…A total of 14 studies were included to analyze the effect of age. We found no statistical difference in the age of the two groups (SMD = 0.085, 95% CI = À0.073-0.189, p = 0.388, 12 Case-control study 346 1100 ☆☆☆ ☆☆ ☆☆ 7☆ Wi 18 Case-control study 142 20 ☆☆ ☆☆ ☆☆ 6☆ Tenforde 13 Case-control study 314 1669 ☆☆☆ ☆☆ ☆☆ 7☆ Hsu 19 Case-control study 85 85 ☆☆ ☆☆ ☆☆☆ 7☆ Blanquart 20 Case-control study 724 5459 ☆☆☆ ☆☆ ☆☆ 7☆ Bollineni 21 Case-control study 14 56 ☆ ☆☆ ☆☆☆ 6☆ Marincu 22 Case-control study 62 62 ☆☆ ☆☆ ☆☆☆ 7☆ Wolff 23 Case-control study 260 507 ☆☆☆ ☆☆ ☆☆☆ 8☆ Kalligeros 24 Case-control study 91 824 ☆☆☆ ☆☆ ☆☆☆ 8☆ Fragoulis 25 Cohort study 101 60 ☆☆☆ ☆☆ ☆☆☆ 8☆ Trunfio 26 Cohort study 55 110 ☆☆☆ ☆☆ ☆☆ 7☆ Safdar 27 Cohort study 45 65 ☆☆☆ ☆☆ ☆☆☆ 8☆ Bouton 28 Cohort study 96 329 ☆☆ ☆☆ ☆☆☆ 7☆ Bosch 29 Case-control study 126 839 ☆☆ ☆☆ ☆☆☆ 7☆ Christensen 30 Case-control study 3346 13,619 ☆☆☆ ☆☆ ☆☆☆ 8☆ Yu 31 Case-control study 23 50 ☆☆☆ ☆☆ ☆☆☆ 8☆ Bayhan 32 Case-control study 38 190 ☆☆☆ ☆☆ ☆☆☆ 8☆ Kustin 33 Case-control study 396 396 ☆☆ ☆☆ ☆☆ 6☆ Toda 34 Case-control study 11 15 ☆☆☆ ☆☆ ☆☆☆ 8☆ Tian 4 Case-control study 88 41 ☆☆☆ ☆☆ ☆☆☆ 8☆ Sayed 35 Case-control study 50 70 ☆☆☆ ☆☆ ☆☆☆ 8☆ Lee 36 Case-control study 174 587 ☆☆☆ ☆☆ ☆☆☆ 8☆ Luo 37 Case-control study 484 1782 ☆☆☆ ☆☆ ☆☆ 7☆ Puhach 38 Case-control study 139 245 ☆☆ ☆☆ ☆☆ 6☆ Whittaker 39 Case-control study 716 2487 ☆☆☆ ☆☆ ☆☆☆ 8☆ Sanghavi 40 Case-control study 149 478 ☆☆☆ ☆☆ ☆☆☆ 8☆ Butt (1) 41 Case-control study 250 250 ☆☆☆ ☆☆ ☆☆☆ 8☆ Butt (2) 42 Case-control study 456 456 ☆☆☆ ☆☆ ☆☆☆ 8☆ Spiera 43 Case-control study 88 2317 ☆☆ ☆☆ ☆☆☆ 7☆ Baltas 44 Case-control study 119 476 ☆☆☆ ☆☆ ☆☆ 7☆ John 45 Case-control study 254 508 ☆☆ ☆☆ ☆☆ 6☆ Jacobson 46 Case-control study 189 471 ☆☆ ☆☆ ☆☆ 6☆ Estofolete …”
Section: Ageunclassified
“…A total of 14 studies were included to analyze the effect of age. We found no statistical difference in the age of the two groups (SMD = 0.085, 95% CI = À0.073-0.189, p = 0.388, 12 Case-control study 346 1100 ☆☆☆ ☆☆ ☆☆ 7☆ Wi 18 Case-control study 142 20 ☆☆ ☆☆ ☆☆ 6☆ Tenforde 13 Case-control study 314 1669 ☆☆☆ ☆☆ ☆☆ 7☆ Hsu 19 Case-control study 85 85 ☆☆ ☆☆ ☆☆☆ 7☆ Blanquart 20 Case-control study 724 5459 ☆☆☆ ☆☆ ☆☆ 7☆ Bollineni 21 Case-control study 14 56 ☆ ☆☆ ☆☆☆ 6☆ Marincu 22 Case-control study 62 62 ☆☆ ☆☆ ☆☆☆ 7☆ Wolff 23 Case-control study 260 507 ☆☆☆ ☆☆ ☆☆☆ 8☆ Kalligeros 24 Case-control study 91 824 ☆☆☆ ☆☆ ☆☆☆ 8☆ Fragoulis 25 Cohort study 101 60 ☆☆☆ ☆☆ ☆☆☆ 8☆ Trunfio 26 Cohort study 55 110 ☆☆☆ ☆☆ ☆☆ 7☆ Safdar 27 Cohort study 45 65 ☆☆☆ ☆☆ ☆☆☆ 8☆ Bouton 28 Cohort study 96 329 ☆☆ ☆☆ ☆☆☆ 7☆ Bosch 29 Case-control study 126 839 ☆☆ ☆☆ ☆☆☆ 7☆ Christensen 30 Case-control study 3346 13,619 ☆☆☆ ☆☆ ☆☆☆ 8☆ Yu 31 Case-control study 23 50 ☆☆☆ ☆☆ ☆☆☆ 8☆ Bayhan 32 Case-control study 38 190 ☆☆☆ ☆☆ ☆☆☆ 8☆ Kustin 33 Case-control study 396 396 ☆☆ ☆☆ ☆☆ 6☆ Toda 34 Case-control study 11 15 ☆☆☆ ☆☆ ☆☆☆ 8☆ Tian 4 Case-control study 88 41 ☆☆☆ ☆☆ ☆☆☆ 8☆ Sayed 35 Case-control study 50 70 ☆☆☆ ☆☆ ☆☆☆ 8☆ Lee 36 Case-control study 174 587 ☆☆☆ ☆☆ ☆☆☆ 8☆ Luo 37 Case-control study 484 1782 ☆☆☆ ☆☆ ☆☆ 7☆ Puhach 38 Case-control study 139 245 ☆☆ ☆☆ ☆☆ 6☆ Whittaker 39 Case-control study 716 2487 ☆☆☆ ☆☆ ☆☆☆ 8☆ Sanghavi 40 Case-control study 149 478 ☆☆☆ ☆☆ ☆☆☆ 8☆ Butt (1) 41 Case-control study 250 250 ☆☆☆ ☆☆ ☆☆☆ 8☆ Butt (2) 42 Case-control study 456 456 ☆☆☆ ☆☆ ☆☆☆ 8☆ Spiera 43 Case-control study 88 2317 ☆☆ ☆☆ ☆☆☆ 7☆ Baltas 44 Case-control study 119 476 ☆☆☆ ☆☆ ☆☆ 7☆ John 45 Case-control study 254 508 ☆☆ ☆☆ ☆☆ 6☆ Jacobson 46 Case-control study 189 471 ☆☆ ☆☆ ☆☆ 6☆ Estofolete …”
Section: Ageunclassified
“…Additionally, phase 3 clinical trial results at 28 days after CanSino vaccination have demonstrated a vaccine efficacy of 58% [1]. Otherwise, little is published about CanSino’s real-world effectiveness in preventing illness, hospitalization, and death; two studies from Malaysia and Pakistan included patients vaccinated with CanSino in national estimates demonstrating vaccine impact [8, 9], but no product-specific vaccine effectiveness estimates have been published to date.…”
Section: Introductionmentioning
confidence: 99%